2020
DOI: 10.1038/s42003-020-0872-x
|View full text |Cite
|
Sign up to set email alerts
|

Miro2 tethers the ER to mitochondria to promote mitochondrial fusion in tobacco leaf epidermal cells

Abstract: Mitochondria are highly pleomorphic, undergoing rounds of fission and fusion. Mitochondria are essential for energy conversion, with fusion favouring higher energy demand. Unlike fission, the molecular components involved in mitochondrial fusion in plants are unknown. Here, we show a role for the GTPase Miro2 in mitochondria interaction with the ER and its impacts on mitochondria fusion and motility. Mutations in AtMiro2's GTPase domain indicate that the active variant results in larger, fewer mitochondria whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…Oikawa et al (2015) used a femtosecond laser to generate shock waves to quantify the physical interaction between chloroplasts and peroxisomes. This same organelle pairing has been analyzed using optical tweezers (Gao et al, 2016), as have ER-Golgi (Sparkes et al, 2009), ER-chloroplast (Andersson et al, 2007) and ERmitochondria interactions (White et al, 2020). Optical tweezers provide submicron accuracy to trap and "target" a single organelle and micro-manipulate its position relative to other structures ( Figure 1D).…”
Section: Measuring Organelle Tethering Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oikawa et al (2015) used a femtosecond laser to generate shock waves to quantify the physical interaction between chloroplasts and peroxisomes. This same organelle pairing has been analyzed using optical tweezers (Gao et al, 2016), as have ER-Golgi (Sparkes et al, 2009), ER-chloroplast (Andersson et al, 2007) and ERmitochondria interactions (White et al, 2020). Optical tweezers provide submicron accuracy to trap and "target" a single organelle and micro-manipulate its position relative to other structures ( Figure 1D).…”
Section: Measuring Organelle Tethering Forcesmentioning
confidence: 99%
“…Membrane contact sites (MCS) are regions at which transient, physical interactions between organelles occur. These interactions allow exchange of molecules such as signals (e.g., calcium, Csordás et al, 2010) and membrane lipids (Michaud and Jouhet, 2019), and are important for regulating the number and positioning of some organelle types (Phillips and Voeltz, 2016;Mueller-Schuessele and Michaud, 2018;White et al, 2020). Direct molecular exchanges between organelles may alternatively be carried out by vesicle-mediated delivery (Scorrano et al, 2019) or by transient interaction between organelles of the same type (e.g., "kiss and run" in mitochondria, Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the situation with fission, obvious orthologues of yeast or mammalian fusion have not been found [ 20 ]. However, recently, the GTPase ATMIRO2 has been investigated in tobacco epidermal cells [ 49 ]. Homologues in yeast (ScGEM1) affect mitochondrial–ER interactions and in mammals (HsMIRO1) affect mitochondrial motility.…”
Section: Mitochondrial Fusionmentioning
confidence: 99%
“…Homologues in yeast (ScGEM1) affect mitochondrial–ER interactions and in mammals (HsMIRO1) affect mitochondrial motility. Evidence was obtained that AtMIRO2 regulates the tethering of mitochondria to the ER, such that ER–mitochondria attachment increases mitochondrial fusion, associated with increased clustering of mitochondria and decreased motility [ 49 ]. It has been shown that actin polymerisation is not required for mitochondrial fusion [ 18 , 50 ], though myosin and microtubule inhibitors reduced fusion [ 18 ].…”
Section: Mitochondrial Fusionmentioning
confidence: 99%
“…Although dysfunction of Arabidopsis MIRO1 caused embryo lethality, elongated mitochondria were detected in pollen tubes [ 69 ]. Interestingly, Arabidopsis MIRO2 knockout plants showed no obvious growth defects, but when there was overexpression of an active MIRO2 variant, larger and fewer mitochondria were observed in stable contact with the ER [ 70 ]. Contrary to the dominant function of MIRO in mitochondrial movement, MIRO might function in a plant-specific manner for both mitochondrial fusion and motility.…”
Section: Interplay Between Mitophagy and Mitochondrial Dynamicsmentioning
confidence: 99%